2023
DOI: 10.1371/journal.pbio.3001983
|View full text |Cite
|
Sign up to set email alerts
|

Early transcriptional and epigenetic divergence of CD8+ T cells responding to acute versus chronic infection

Abstract: During a microbial infection, responding CD8+ T cells give rise to effector cells that provide acute host defense and memory cells that provide sustained protection. An alternative outcome is exhaustion, a state of T cell dysfunction that occurs in the context of chronic infections and cancer. Although it is evident that exhausted CD8+ T (TEX) cells are phenotypically and molecularly distinct from effector and memory CD8+ T cells, the factors regulating the earliest events in the differentiation process of TEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Recently, using a mouse LCMV infection model, Chang et al discovered that in comparison to CD8 + T cells that had undergone their first division in response to LCMV-Arm, CD8 + T cells that had undergone their first division in response to LCMV-Cl13 expressed higher levels of EZH2. [46] Examining this and additional public human and mouse bulk and single-cell RNA seq datasets, we observed that rather than being associated with a particular differentiation stage, the expression of EZH2 is tightly correlated with T cell proliferation —actively dividing cells of diverse phenotypes harbor the highest levels of Ezh2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using a mouse LCMV infection model, Chang et al discovered that in comparison to CD8 + T cells that had undergone their first division in response to LCMV-Arm, CD8 + T cells that had undergone their first division in response to LCMV-Cl13 expressed higher levels of EZH2. [46] Examining this and additional public human and mouse bulk and single-cell RNA seq datasets, we observed that rather than being associated with a particular differentiation stage, the expression of EZH2 is tightly correlated with T cell proliferation —actively dividing cells of diverse phenotypes harbor the highest levels of Ezh2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on murine tissue-resident memory T cells demonstrated that S1pr5 induction is directly controlled by T-bet and Zeb2 (81). Additionally, CD8 + T cells from chronic infection models of LCMV exhibit a higher frequency of T-bet + cells and higher T-bet expression levels than those from acute infection models (75). These reports further strengthen the findings from our DNA methylation dataset and suggest that in T(CMV) cells, the selectively demethylated genes TBX21 , ZEB2 , and S1PR5 may jointly coordinate the effector function of antigen-specific CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent report showed that even during their early phase of differentiation, CD8 + T cells responding to acute and chronic infections displayed distinct transcriptional and epigenetic landscapes (75). Among the unique epigenetic signature genes of T(CMV) cells identified in the present study, KLRD1, TBX21 (coding for T-bet), and ZEB2 have already been reported to regulate functional properties of memory CD8 + T cells and were found to be upregulated in chronic infections or exhausted CD8 + T cells (14,(75)(76)(77)(78)(79)(80). Furthermore, we noted that DMRs linked with S1PR5, a migratory receptor that is expressed by circulating memory CD8 + T cells, but selectively downregulated in tissue-resident memory CD8 + T cells (81-83),…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric cell division in CD8 + T cells results in the unequal inheritance of different cell cargoes that culminates in divergent transcriptomes between daughter cells [27][28][29][30] . We aimed to broaden our 4 understanding of early events of asymmetric segregation by assessing the global proteome of firstdaughter CD8 + T cells.…”
Section: Divergent Proteome and Mitochondrial Inheritance In Cd8 + T ...mentioning
confidence: 99%
“…In other studies, including our own, transcriptional profiling of CD8 + T cell populations following one cycle of cell division was performed using bulk and single cell strategies [27][28][29][30]44 . However, these reports either relied on the expression of surface markers and reporter genes with the caveat of their dynamic expression to identify effector-like and memory-like cell daughters.…”
Section: Inheritance Of Aged Mitochondria Counteracts Cellular Quiesc...mentioning
confidence: 99%